Comparing the Rat Grimace Scale and a composite behaviour score in rats - Klune, Cassandra B. (PLoS One, 2019)
There is a growing interest in the use of voluntarily displayed ongoing behaviours in laboratory animals to assess the pain experience. In rats, two behavioural pain scales, the Rat Grimace Scale (RGS, a facial expression scale) and a composite behaviour score (CBS, a behavioural ethogram reliant on postural changes), are both promising pain assessment methods. Both scales have been used to assess pain in a laparotomy model, however, they have never been compared directly and the knowledge of how different analgesics may affect these two scales is limited. This study aimed to provide a comparison to discriminate the temporal and analgesic response in a laparotomy model. Female Wistar (n = 26) and Sprague Dawley rats (n = 26) were block randomized to receive saline, meloxicam (2 mg/kg) or buprenorphine (0.05 mg/kg) 30 minutes before laparotomy. Rats were video-recorded before surgery (BL) and at 30, 150, 270, and 390 minutes post-operatively. Videos were assessed according to both scales by a trained, blinded observer. Both CBS and RGS scores increased significantly at all post surgical timepoints in the saline group. Both buprenorphine and meloxicam reduced CBS scores to baseline levels following laparotomy; however, RGS scores were only reduced following buprenorphine. RGS scores in the meloxicam group remained similar to scores of the saline group. These findings suggest that the CBS and RGS differ in their sensitivity to discriminating analgesic effects.